Effects of Satureja Khuzestanica supplementation on glycemic indices and lipid profile in type 2 diabetes patients: a randomized controlled clinical-trial - Sajjad Roosta; Fatemeh Ghasemi; Yaser Mokhayeri; Saeed Choobkar; Mohammad Reza Nikbakht; Ebrahim Falahi (BMC, 2024)
Abstract Background Several studies showed the hypoglycemic and hypolipidemic effects of Satureja Khuzestanica (SK) in animal models. This study aimed to determine the effect of SK supplementation on glycemic and lipid outcomes of patients with type 2 diabetes mellitus (T2DM). Methods The study was designed as a double-blind, placebo-controlled, randomized clinical trial using block randomization. Seventy-eight T2DM patients were randomly assigned to intervention (n = 39) or placebo (n = 39) groups. They received SK or placebo in 500 mg capsules daily for 12 weeks. Anthropometric, blood pressure, liver enzymes, glycemic, and lipid outcomes were measured before and after the intervention. Results At baseline, there were no significant differences in age, sex, or glycated hemoglobin (HbA1c) levels between the groups. SK supplementation led to a significant decrease in FBS (-12.6 ± 20.7 mg/dl in the intervention group versus 3.5 ± 31.9 mg/dl; p = 0.007), HbA1c (-0.28 ± 0.45 in the intervention group versus 0.11 ± 0.54% in the placebo group; p = < 0.001), insulin (-1.65 ± 6.18 in the intervention group versus 2.09 ± 5.90 mIU/L in the placebo group; p = 0.03), total cholesterol (-14.6 ± 21.1 mg/dl in the intervention group versus 8.2 ± 30.9 mg/dl in the placebo group; p < 0.001), LDL-cholesterol (-4.6 ± 15.2 mg/dl in the intervention group versus 5.8 ± 14.6 mg/dl in placebo group; p < 0.001) levels, and significant increase in HDL-cholesterol (3.9 ± 4.9 mg/dl in the intervention group versus 0.9 ± 5.2 mg/dl in placebo group; p = 0.005). Conclusion Based on the study results, SK supplementation may improve glycemic indices and lipid profile of patients with T2DM. Our findings may provide novel complementary treatments without adverse effects for diabetes complications. These results need to be further confirmed in clinical trials. Registration : This trial has been registered in the Iranian Registry of Clinical Trials (IRCT ID: IRCT20190715044214N1, registration date: 21/02/2021).